Gastrointestinal Stromal Tumor: A Case Report - Krstevski, Stefan (International Journal of Medical Students, 2016)
Background: Gastrointestinal stromal tumor (GIST) is a rare gastrointestinal tumor but the most common mesenchymal tumor. It originates in the interstitial cells of Cajal, which on their own membranes have a specific antigen designated as CD117 or KIT receptor, a reliable indicator of tumor detection and therapy. Case: We reported a case of a 63-year-old male patient, who presented with symptoms of severe abdominal pain, discomfort, and secondary anemia. After a physical examination and a CT scan of the abdomen with angiography, the presence of a large tumor in the right hypochondrium was detected. Blood tests showed a high C-reactive protein and low hemoglobin. The patient had an exploratory laparotomy on his abdomen with complete removal of the tumor growth, which was then histologically analyzed. The obtained result from the histological analysis showed a high-degree of GIST. Conclusion: Early diagnosis of GISTs is of paramount importance to reduce mortality rate. This requires good background in pathobiology and knowledge of the physical manifestations of this malignant tumor. When this is combined with various imaging techniques, it becomes the gold standard method for GIST diagnosis.